Penggunaan Media Pembelajaran Audio Visual Untuk Meningkatkan Kemampuan Membaca Al Qur’an Siswa di SD Negeri 2 Kedondong - Kristina, Marilin; Sari, Ruly Nadian; Sari, Noca Yolanda; Gumanti, Miswan (CV. Creative Tugu Pena, 2022)
This study aims to describe how the application of audio-visual learning media in improving the ability to read the Qur'an in Islamic education subjects at SD Negeri 2 Kedondong. This research is included in classroom action research or action research. The study material for cycle I and cycle II is about reading Al-Qur'an Surah Al-Maun with tartil. This data collection is carried out using an observation/assessment format that has been prepared, including careful observation of matters relating to student activities while carrying out the action. Based on the analysis of the test results of cycle I and cycle II in the learning process and learning to read the Qur'an, grade 5 students of SD Negeri 2 Kedondong experienced an increase in each cycle, meaning that students had understood the material and practice of PAI learning. So it can be concluded that the learning process using audio-visual learning media affects PAI learning and the use of audio-visual learning media can improve the ability to read the Qur'an in 5th grade students of SD Negeri 2 Kedondong Keywords: Learning Media, Improving Learning Al Quran, Learning Audio Visual